Advances in High-Efficiency LLC Resonant Converters - Jung, Jeehoon (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book covers several research items related to LLC resonant converters, which were published in a Special Issue of Energies on the subject area of "Advances in High-Efficiency LLC Resonant converter". It focuses on emerging power electronic topologies related to the LLC resonant converter, and its design methodology and control algorithms. Topics of interest include LLC resonant topologies, resonant tank design methodology for high efficiency, power loss analysis in LLC resonant converters, high-frequency magnetics for resonant converters, wide band-gap devices applied to LLC resonant converter, and advanced control algorithm for LLC resonant converter.